The double filial bond rule in crisis (Nueva Epoca, 2020)
The determination of the paternal and maternal ties is not a quantitative but a qualitative question, within each source of the Filiation. In this framework, the rule of the mandatory double bond is incorrect. In Filiation by nature, the links are necessarily two, since they are determined by the generation from the intersexual act. In filiation by procreational will, the links are limited to those who expressed their prior consent; This limitation violates the right to identity and must be removed. In adoptive filiation, multiple parenthood is possible because it is based on the recognition of the origin that precedes the adoption. The best interests of the child do not alter the rules for determining links with their parents, although it is relevant to establish their functions and duties, or to designate third parties under legal care figures. The sole will to be a father or mother or to be a child is not the cause of the legal relationship of filiation, although its incidence varies in each of the sources of filiation.
Keywords: filiation; legal ties; affective bonds